2008
DOI: 10.1016/j.camwa.2007.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Buoyancy convection in a cavity with mutually orthogonal heated plates

Abstract: Buoyancy driven convection in a square cavity induced by two mutually orthogonal arbitrarily placed heated thin plates is studied numerically under isothermal and isoflux boundary conditions. The flow is assumed to be two-dimensional. The coupled governing equations were solved by the finite difference method using the Alternating Direction Implicit technique and Successive Over Relaxation method. The steady state results are depicted in terms of streamline and isotherm plots. It is found that the resulting co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The values of the Nusselt number corresponding to all these situations can be found in Table III (where it is shown that the intensity of heat exchange between the surface of the step and the fluid increases as the Rayleigh number becomes higher). Interestingly, the set of values reported there also indicates that the mechanism of the Hadley type (being operative near the vertical side of the step) is much more efficient in transporting heat than that due to a heating-from-below condition at work along the horizontal side of the step (this finding being in line with other studies where square cavities with a heated plate built in vertically or horizontally or with a finned heated plate were considered, see, e.g., Oztop et al [58]; Saravanana et al [59]; Saravanan and Sivaraj [60]; Nadjib et al [61]; we will come back to this concept in Sect. 3.1.3).…”
Section: Patterning Behavior For the Cavity With Adiabatic Floorsupporting
confidence: 83%
“…The values of the Nusselt number corresponding to all these situations can be found in Table III (where it is shown that the intensity of heat exchange between the surface of the step and the fluid increases as the Rayleigh number becomes higher). Interestingly, the set of values reported there also indicates that the mechanism of the Hadley type (being operative near the vertical side of the step) is much more efficient in transporting heat than that due to a heating-from-below condition at work along the horizontal side of the step (this finding being in line with other studies where square cavities with a heated plate built in vertically or horizontally or with a finned heated plate were considered, see, e.g., Oztop et al [58]; Saravanana et al [59]; Saravanan and Sivaraj [60]; Nadjib et al [61]; we will come back to this concept in Sect. 3.1.3).…”
Section: Patterning Behavior For the Cavity With Adiabatic Floorsupporting
confidence: 83%
“…Unlike in [24,25] we have plate-plate and plate-wall temperature ratios. We introduce them through the non-dimensional temperature ratios…”
Section: Problem Formulation and Solution Proceduresmentioning
confidence: 87%
“…The grids 101 × 101 and 121 × 121 gave almost identical results. Hence considering both the accuracy and the computational time, the computations were all performed with a 101 × 101 grid and further details including validation of the code developed and grid independency study can be seen in our earlier works [24,25].…”
Section: Problem Formulation and Solution Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Kakarantzas et al [11] used a direct numerical method with a fractional semi-implicit scheme approach to simulate natural hydromgnetic convection in a vertical cylindrical cavity with sinusoidal top wall temperature variation. Saravanan et al [12] examined numerically the two-dimensional buoyancy-driven convection in a square cavity with isoflux and isothermal boundary conditions. Walker and Homsy [13] investigated buoyancy-driven convection in a porous cavity.…”
mentioning
confidence: 99%